Morphological description of Chaetostoma thomsoni, an endemic fish from Colombia - Ayala-Combariza, Julieth; Muñoz-Duque, Julián David; Tamayo-Arango, Lynda Jhailu; Chaparro-Gutiérrez, Jenny Jovana; Franco-Montoya, Luz-Natalia (Revista Colombiana de Ciencias Pecuarias, 2025)
Background: The Porce River basin, where the Porce II and Porce III reservoirs are located, harbors a wide diversity of endemic ichthyofauna, many of which lack detailed anatomical and histological descriptions. Chaetostoma thomsoni Regan, 1904 (Siluriformes: Loricariidae), commonly referred to as striped rubbernose plecostomus, cucha, or carachama in South America, is a teleost fish that inhabits fast-flowing rivers and streams with moderate slopes. This species is abundant in the Magdalena and Cauca River basins in Colombia. Objective: To characterize the anatomical and histological features of the skin and internal organs of C. thomsoni from the Porce River basin. Methods: Thirty-seven specimens of C. thomsoni were collected from streams using electrofishing and cast nets. Fish were euthanized with Eugenol solution (300 mg/L), preserved in 10% buffered formalin, labeled, and stored individually in Falcon tubes. Samples were processed at the Animal Anatomy Laboratory of the University of Antioquia, Colombia, where biometric measurements, dissections, and tissue sampling were performed. Results: A complete morphometric analysis was carried out, together with a comprehensive description of the skin and internal anatomy, including macro- and microscopic characterization of the intestine, hepatopancreas, spleen, kidney, urinary bladder, and gonads, among other organs. The findings provide reference data on the health status and applied anatomy of the species, including the identification of an optimal cardiopuncture site for blood sampling. A notable observation was the cephalic kidney, exhibiting a cranially bifurcated morphology partially surrounding the brain. Both cephalic and caudal regions of the kidney contained interstitial hematopoietic tissue and displayed endocrine and immunological functions. In addition, Stannius corpuscles were observed as two distinct nodules in the caudal kidney. Conclusion: This anatomical and histological characterization provides a baseline for future studies aimed at advancing the knowledge and conservation of endemic Colombian ichthyofauna.